FAKTOR-FAKTOR YANG MENENTUKAN PARA MAHASISWA MEMILIH KULIAH DI UNIVERSITAS BUNDA MULIA DENGAN METODE FAKTOR ANALISIS - Rudy Santosa Sudirga (Business Management Journal, 2017)
Over the last three years the number of students choosing Bunda Mulia University as a university choice has steadily increased. This phenomenon is clearly portrayed from the results of a study that was undertaken to determine factors that influence choices that senior high school students make decision to enter university. This research examines this phenomenon in the context of students’ choice of a university. Results of a survey of students showed that parents, along with other family and friends, were the most influential sources of information. Factor analysis is a precise method to perform this research, since factor analysis will generate factors that demonstrate acceptable internal consistency and describe the important influences in shaping university preferences. The correlations between the factors and Bunda Mulia University as first university choice are in the expected directions of this research and provide evidence for construct validity of the questionnaire. Key Words,Factors, Influence, and Choices.